Dormitory management in islamic boarding school educational institutions - Nazarullah Mawardi Arsyad; Maemunah Sa’diyah; Muhammad Chafidz Ali Wafa (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
Dormitory management in Islamic boarding schools is crucial for creating a conducive learning environment that supports the educational activities of students. This management process involves structured and systematic planning, organizing, actuating, and controlling. Planning includes setting goals and developing activity programs that support student development. Organizing involves establishing a dormitory organizational structure with clear roles and responsibilities for both administrators and students. Actuating entails effective leadership, motivation, communication, and the formation of solid work teams to implement the dormitory programs. Controlling is conducted through internal and external methods to monitor the performance of administrators and students, ensuring alignment with the values and traditions of the boarding school. Through effective management, the dormitory becomes a safe, comfortable, and educational place, thereby fostering students who are morally upright, disciplined, and ready to face societal challenges.